Topological Transitivity of Shift Similar Operators on Nonseparable Hilbert Spaces. (18th October 2021) - Zagorodnyuk, Andriy; Novosad, Zoriana
Abstract : In this paper, we investigate topological transitivity of operators on nonseparable Hilbert spaces which are similar to backward weighted shifts. In particular, we show that abstract differential operators and dual operators to operators of multiplication in graded Hilbert spaces are similar to backward weighted shift operators.